2019
DOI: 10.3389/fmicb.2018.03220
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Oral and Gut Pathogens in Full Thickness Colon of Colitis Patients: Implications for Colon Motility

Abstract: Impaired colon motility is one of the leading problems associated with inflammatory bowel disease (IBD). An expanding body of evidence supports the role of microbiome in normal gut function and in progression of IBD. The objective of this work is to determine whether diseased full thickness colon specimens, including the neuromuscular region (critical for colon motility function), contain specific oral and gut pathogens. In addition, we compared the differences in colon microbiome between Caucasians (CA) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…In general, the group of gut microbes associated with a good health outcome are identified as “potential beneficial bacteria,” 33 such as short‐chain fatty acid (SCFA)‐producing bacteria ( Bacteroides, Faecalibacterium, Phascolarctobacterium, Roseburia, Bifidobacterium, Blautia, etc) 34‐36 . Those could potentially lead to development or progression of noncommunicable diseases are identified as “potential detrimental microbes,” 33 such as enteric pathogens and opportunistic pathogens ( Escherichia‐Shigella , Klebsiella , Enterococcus , Streptococcus , etc) 37‐39 …”
Section: Methodsmentioning
confidence: 99%
“…In general, the group of gut microbes associated with a good health outcome are identified as “potential beneficial bacteria,” 33 such as short‐chain fatty acid (SCFA)‐producing bacteria ( Bacteroides, Faecalibacterium, Phascolarctobacterium, Roseburia, Bifidobacterium, Blautia, etc) 34‐36 . Those could potentially lead to development or progression of noncommunicable diseases are identified as “potential detrimental microbes,” 33 such as enteric pathogens and opportunistic pathogens ( Escherichia‐Shigella , Klebsiella , Enterococcus , Streptococcus , etc) 37‐39 …”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were as follows: recent (<2 months prior) use of any antibiotic or probiotic therapy, recent (<2 weeks prior) use of any proton pump inhibitors, known any other enteritis, 9,10 known autoimmune condition, significant gastrointestinal disorder, age <18 years, vegetarians, abnormal BMI value (<18.5 or >24), known history of any other cancer, 12 and significant liver, renal, or peptic ulcer disease.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Previous studies have shown that the invasive potential of gut mucosa-derived F. nucleatum positively correlated with CD status of the host (Zhou et al, 2016;Dinakaran et al, 2018). To verify the potential relationship between gut microbiota alterations and CD, we compared three inflamed tissues from patients with active CD (ACD) and three inflamed tissues from patients with remitted CD (RCD) by HiSeq 2500 sequencing.…”
Section: F Nucleatum Is Abundant In Crohn's Disease Tissues and Is Lmentioning
confidence: 99%